Development of Amorphous/Microcrystalline Silicon Tandem Thin-Film Solar Modules with Low Output Voltage, High Energy Yield, Low Light-Induced Degradation, and High Damp-Heat Reliability. (16th March 2014) - Tsai, Chin-Yi; Tsai, Chin-Yao
Abstract : In this work, tandem amorphous/microcrystalline silicon thin-film solar modules with low output voltage, high energy yield, low light-induced degradation, and high damp-heat reliability were successfully designed and developed. Several key technologies of passivation, transparent-conducting-oxide films, and cell and segment laser scribing were researched, developed, and introduced into the production line to enhance the performance of these low-voltage modules. A 900 kWp photovoltaic system with these low-voltage panels was installed and its performance ratio has been simulated and projected to be 92.1%, which is 20% more than the crystalline silicon and CdTe counterparts.